Spatial analysis of stunting risk factors in Central Java, Indonesia: A geographically weighted regression approach (2023 data) - Sylvia Anjani; Faik Agiwahyuanto; Maulana Tomy Abiyasa (Intelektual Pustaka Media Utama, 2026)
The 2022 Indonesian Nutritional Status Survey (SSGI) reported a stunting prevalence of 20.8% in Central Java. Although various studies have examined its risk factors, few have applied a spatial perspective. This study aims to analyze regional variations in stunting risk factors and their contribution to rising stunting rates. This is a quantitative explanatory study employing the geographically weighted regression (GWR) method. Secondary data were obtained from the Central Java Health Profile and Badan Pusat Statistik Indonesia (BPS) in 2023, using a total sampling of 35 districts/cities. The GWR results indicated that chronic energy deficiency (CED; β = 0.0014, p = 0.068) and exclusive breastfeeding (β = 0.0791, p = 0.087) were marginally positively associated with stunting. Low birth weight (LBW) showed a significant positive association (β = 0.1009, p = 0.041), while access to improved sanitation had a strong negative effect (β = -0.1882, p = 0.004). Iron supplementation (≥90 tablets) was not significant (β = -0.0629, p = 0.134), whereas access to improved drinking water was positively and significantly correlated with stunting (β = 0.3778, p = 0.028). These findings contradict existing theories, particularly where higher rates of exclusive breastfeeding and access to clean water are unexpectedly associated with increased stunting in several regions. This suggests the need for further in-depth investigation in those areas to better understand the underlying factors.